Deformation and toughness behavior of β -type titanium alloys comprising C15-type Laves phase. (September 2020) - Rabadia, C.D.; Liu, Y.J.; Jawed, S.F.; Wang, L.Q.; Sun, H.; Zhang, L.C.
Abstract: Laves phases are effective in tailoring the mechanical properties of alloys used for structural engineering applications. Therefore, it is an emerging research significance to investigate the deformation features of alloys comprising a Laves phase. In this work, the Ti–33Zr–xFe–yCr (x = 5, 7 wt% and y = 2, 4 wt%) alloys were designed in such a way that a Laves phase would form in the investigated Ti–33Zr–xFe–yCr alloys and later, cast by cold crucible levitation melting. All the as-cast alloys exhibit a face-centered cubic C15-type Laves phase along with a dominant β phase. The volume fraction of C15 Laves phase increases as the quantities of Fe and Cr increase in the Ti–33Zr–xFe–yCr alloys. Further, the volume fraction of C15 Laves phase influences the size of the deformation zone around the indentations and hardness of the investigated Ti–33Zr–xFe–yCr alloys. Vickers microindentation technique was used at the three different loads to examine the deformation features (around the indentations) of the as-cast alloys. In this work, Ti–33Zr–5Fe–2Cr shows large plastic strain (37.0%) in compression testing and high (true) yield strength (1, 083 MPa) and hardness (3.50 GPa),  whereas Ti–33Zr–7Fe–4Cr demonstrates the highest (true) yield strength (1, 285 MPa), hardness (4.08 GPa), and the lowest size of the deformation zone around the indentations at three different indentation-loads. Moreover, the indentation-based fracture toughness of Ti–33Zr–7Fe–2Cr and Ti–33Zr–7Fe–4Cr were estimated based on the various relevant models proposed in the established literature. Highlights: Volume fraction of Laves phase significantly affects mechanical properties. C15-type Laves phase shows the superior strengthening ability in this work. Size of deformation zone relates inversely with the volume fraction of Laves phase. Fracture toughness decreases as the volume fraction of Laves phase increases. Ti–33Zr–5Fe–2Cr shows a better blend of strength, plasticity and hardness.